Asymmetric Effects of Air Pollution and Public Health Expenditure on Mortality in South Africa: Does Access to Electricity Matter? - Emmanuel Aondongusha Asue (GHMJ (Global Health Management Journal), 2026)
Background: There appears to be a decline in public health expenditure per capita amid high levels of air pollution in South Africa, and it is not clear whether this has a toll on the country's crude mortality rate. This study examined the asymmetric effects of particulate matter air pollution (PM2.5) and public health expenditure on crude mortality rates in South Africa. Coal is the major source of electricity in South Africa, and it generates high levels of PM2.5. This has implications for human respiratory systems and airway health, potentially affecting mortality rates despite increases in public health expenditure. Aims: The study examined whether increases or decreases in air pollution and public health expenditure per capita significantly affect mortality rate in South Africa, and how access to electricity and income per capita affect mortality amidst these non-linear interactions. Methods: The study employed annual time-series data covering 35 years (1990 to 2024). The study adopted the Nonlinear Autoregressive Distributed Lag (NARDL) cointegration framework, which separates positive and negative shocks to air pollution and health expenditure and allows estimation of the long- and short-run effects of both types of shocks on mortality. The study also explicitly included the percentage of the population with access to electricity to examine the effect of access to clean energy on the pollution-mortality relationship. The study also used national per capita income to assess its influence on mortality rates in South Africa. Results: The results show a statistically significant long-run effect of air pollution on mortality. Health expenditure per capita, however, did not produce any significant asymmetric effects on the crude mortality rate, both in the short-run and long run. However, access to electricity has a statistically significant positive effect on mortality, indicating that increased electricity access is a positive and significant factor in productivity, but may also co-evolve with energy-use patterns that require careful environmental management. Mortality is negatively associated with GDP per capita, consistent with the epidemiological transition hypothesis. The error-correction term verifies the quick adjustment towards the long-run equilibrium, indicating that about 90.4% of the disequilibrium is corrected each year. Conclusion: The study concludes that while positive and negative shocks in public health expenditure did not significantly affect the mortality rate, negative shocks in air pollution did. These findings underscore the need for the government of South Africa to work towards a clean energy transition, target health spending toward pollution-related respiratory illnesses, improve citizens’ incomes, and control air pollution to reduce mortality rates.